Kreativitas Guru Penjas dalam Memodifikasi Sarana dan Prasarana Penjas Sekolah Dasar di Kecamatan Kranggan - Pradanto, Andrean Denni; Darmawan, Agus (Indonesian Journal for Physical Education and Sport, 2023)
The focus of this research is to find out the various modifications of facilities and infrastructure for elementary school physical education teachers in Kranggan District. This research is a narrative research type with qualitative descriptive analysis, the research sample used a sample of 10 elementary schools in Kranggan District, 1 school was taken in each village. Retrieval of data using interview techniques, observation, and questionnaires. Based on the results of the study, from a total sample of 10 physical education teachers, the data obtained from the modifications made by the teacher to physical education facilities and infrastructure in each scope are as follows: the scope of basic movement is 55.7%, the scope of development activities is 75%, the scope gymnastic activity by 10%, rhythmic activity by 0%, game and sports activity by 37.3%, and athletic activity by 31.3%. The results of the research that has been carried out can be concluded that the creativity of physical education teachers in modifying infrastructure is still lacking, so that there are some learning materials that are not taught to students.